'You only have one chance to get it right': A qualitative study of relatives' experiences of caring at home for a family member with terminal cancer. (June 2015) - Totman, Jonathan; Pistrang, Nancy; Smith, Susan; Hennessey, Susan; Martin, Jonathan
Background: Relatives looking after a terminally ill family member at home face numerous challenges. Studies into relatives' experiences of home caregiving have been criticised for their descriptive nature and lack of theoretical underpinnings. Aim: To explore the emotional challenges faced by home caregivers, and their experiences of healthcare professionals, from the perspective of existential psychology. Design: A qualitative study using semi-structured interviews. Transcripts were analysed thematically using the Framework approach. Setting/participants: The study took place within an inner-city London hospice. Participants ( n  = 15) were recently bereaved adult relatives of cancer patients who cared for their family member at home. Results: Participants' experiences of being a caregiver and of professional support were highly varied. The analysis generated 15 themes which were organised into a framework based on Yalom's four 'existential conditions': responsibility (e.g. 'being the linchpin of care'; 'you only have one chance to get it right'), isolation (e.g. 'being on my own', 'being held in mind'), death (e.g. 'knowing but not knowing') and meaningfulness (e.g. 'giving something back', 'acceptance and gratitude'). Healthcare professionals were perceived as influential in both helping and hindering relatives in meeting the challenges they faced. Conclusion: Existential psychology provides a theoretical perspective from which to understand the psychological complexity of the emotional challenges home caregivers face and a framework which may usefully inform research and clinical practice. Professionals' attentiveness to caregivers' needs can have powerful effects in assuaging anxiety, reducing isolation and enabling relatives to connect with the meaningfulness of caregiving.